Influence of tungsten on passivity breakdown and repassivation of 25CR super duplex stainless steel - Torres, C.; Johnsen, R.; Kappes, M.; Iannuzzi, Mariano (2018)
© 2018 by NACE International. Super duplex stainless steels are ferritic-austenitic stainless steels with 25 wt% Cr and a pitting resistance equivalent (PRE) = 40. Even though other elements, such as Cr and Mo, have been studied in much more detail than W, research has shown that an optimal composition exists, in which W in solid solution improves localized corrosion resistance. Outside this range, W is ineffective or even detrimental. However, the mechanisms by which W improves localized corrosion resistance in stainless steels are unclear. For example, debate still exists as to whether W enhances passivity or facilitates repassivation. In this work, two super duplex stainless steels were investigated: a W-free (UNS S32750) and a 2.1 wt% W-containing (UNS S39274) grade. The first goal was to study differences in the overall localized corrosion resistance; while the second objective was to gain an insight into the mechanisms by which W affects the localized corrosion performance of super duplex stainless steels. The work was divided into two parts. Firstly, anodic potentiodynamic polarization curves were conducted in different simulated pit environments at various temperatures. Two simulated pit solutions were tested: 1 M HCl and 7 M LiCl adjusted to a pH of 0. In the second part, crevice repassivation potentials were measured using the potentiodynamic-galvanostatic-potentiodynamic technique in 3.5 wt% NaCl pH = 6.5 solution. This investigation will provide evidence regarding the influence of W in passive film stability and repassivation kinetics.